Integrasi Pemikiran Al-Farabi dan Konsep Nur Muhammad terhadap Asal Mula Semesta dalam Konteks Sains Kontemporer - Miswinda; Tajuddin, Amri; Abdullah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study examines the relevance of Islamic metaphysical thought—particularly Al-Farabi’s theory of emanation and the concept of Nur Muhammad—to the development of modern cosmological theories such as the Big Bang. The research aims to integrate these two conceptual frameworks with modern cosmology, which emphasizes the origin of the universe through physical processes such as the initial singularity and the great primordial explosion (Big Bang). This study employs a qualitative approach using descriptive-comparative analysis of Islamic philosophical texts and scientific literature in modern cosmology. Data were collected through a literature review of primary and secondary works of Al-Farabi, classical Islamic theological texts, and recent scholarly articles from reputable journals. The findings indicate that Al-Farabi’s theory of emanation parallels hierarchical evolutionary processes in modern cosmology, while the concept of Nur Muhammad offers a spiritual dimension to scientific understandings of cosmic creation. The contribution of this research lies in providing a new framework that bridges classical Islamic philosophical thought with contemporary science, thereby forming a basis for multidisciplinary dialogue between religion, philosophy, and science. It is expected that this study will enrich academic discourse on the harmony between faith and reason in addressing fundamental questions about the existence of the universe.